Design of an Android-based Prayer Guidance Application Based on Al-Quran and Sunnah - Novi Hendri Adi; Abdul Somad; Farid Kassimov; Abzal Kuanyshuly (Researcher and Lecturer Society, 2023)
Prayer is the cornerstone of religion, and it is an obligation for Muslims who have reached the age of accountability. Prayer is a great act of worship, because it is a direct command from Allah ta'ala to Muslims, whose command was directly received by the Messenger of Allah (peace and blessings of Allah be upon him) without the mediation of Gabriel (peace be upon him) at Sidratul Muntaha on the occasion of Isra' and Mi'raj. Prayer is the first thing that will be judged on the Day of Judgement, as the Messenger of Allah (peace and blessings of Allah be upon him) said: